Assessing the potential for Banana Guards - O'Brien, Justin (Peter Justin), (SAGE Business cases., 2022)
Serial entrepreneur Gavin Megnauth has been offered the opportunity to purchase an exclusive three-year UK sales franchise for an innovative plastic carrying case for bananas. He loves the novelty Banana Guard concept, is sure they will be popular, but is worried that the franchise fee is too high. Should he take the plunge? This interdisciplinary case uses five questions to facilitate students to develop an outline marketing plan from fundamental customer insights and analytically assess the marketing budget and business opportunity using financial models. Initially students consider the various challenges of eating fresh fruit on the go. Students are invited to use their own experience in discussion to discern key fruit consumption pain points and consider what problems the Banana Guard might solve. Using limited information, students will need to apply relevant financial and accounting techniques to conduct a break-even analysis to help the entrepreneur evaluate the opportunities and risks of this franchise. Having linked observed product features with customer benefits, students should then be able to start formulating ideas for an appropriate marketing campaign, with due consideration of Banana Guard's competition. The final question invites students, if they were in the case protagonist Gavin's shoes, to make a decision on this attractive business opportunity.